Y-65=-79

Simple and best practice solution for Y-65=-79 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-65=-79 equation:


Simplifying
Y + -65 = -79

Reorder the terms:
-65 + Y = -79

Solving
-65 + Y = -79

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '65' to each side of the equation.
-65 + 65 + Y = -79 + 65

Combine like terms: -65 + 65 = 0
0 + Y = -79 + 65
Y = -79 + 65

Combine like terms: -79 + 65 = -14
Y = -14

Simplifying
Y = -14

See similar equations:

| 1+2(m+4)=29 | | 6b+6=4 | | 5x+2y=-21 | | 1/2x188 | | 1/2(288) | | j/3+6=10 | | 13(x-1)+8(x-3)=6x+7-5x | | y=17x-51 | | 13=2s-66 | | 2p-5+2p=35 | | 2.48=3.1z | | 18-9x=21x-22 | | 3.72=y/1.5 | | I-15=-22 | | X^6-25=0 | | 7.2y-3.25=17 | | 0.4(2n-3)=0.2n | | (6x^2-53x-10)/(x-8) | | -10p+15=-25 | | 500=30x+2.50(x-150) | | 8(2-2k)+8(8k+3)=-56 | | a=1/2(16x18) | | 8(3x+4)-2x-5-7x=20 | | 8x+3(2x+1)=7 | | 5k-3k=-6 | | 6p-12=-6 | | -21=(19/-3)+3 | | 40x-25y= | | n-(-1)=-87 | | 5x-x=-q | | 2e-4e=16 | | 4/(v-5)=-3 |

Equations solver categories